Mucuna pruriens seeds extract boosts growth, immunity, testicular histology, and expression of immune-related genes of mono-sex Nile tilapia (Oreochromisniloticus). Issue 127 (August 2022) - Elabd, Hiam; Faggio, Caterina; Mahboub, Heba H.; Emam, Mahmoud Abdelghaffar; Kamel, Samar; El Kammar, Reda; Abdelnaeim, Noha S.; Shaheen, Adel; Tresnakova, Nikola; Matter, Aya
Abstract: Nutraceuticals have received increased attention in sustainable aquaculture . Consequently, the present study aimed to evaluate the dietary effects of Mucuna pruriens (MP) seed extract on growth performance, immune status, hepatic function, biochemical profiles, gonadal histology, and expression of immune-related genes in mono-sex Nile tilapia ( Oreochromis niloticus ). Fish were allocated into four groups and received MP at rates of 0 (control), 2, 4, and 6 g/kg diet, respectively, for 90 days. The results revealed that MP significantly ( P< 0.05) modulated growth performance (specific growth rate, final length, and length gain rate, body mass gain, and feed conversion ratio), lysozyme activity, and liver enzymes (AST, ALT). However, a non-significant effect on nitric oxide (NO) or immunoglobulin M (IgM) levels was detected, whereas the dietary inclusion of MP had a hypoglycemic effect. In terms of plasma globulin, albumin, globulin/albumin ratio, and cortisol, the MP receiving groups showed insignificant difference ( P< 0.05) when compared to controls, except for the 2 g MP-supplemented group. The lower inclusion concentration of MP (2 g/kg diet) demonstrated the best result ( P  < 0.05) for gonadosomatic index (GSI) and plasma testosterone level that was consistent with the histological findings reflecting an improvement in the testicular development compared with the control group. Expressions of complement component (C5) and interleukin 1-β ( IL-1β ) genes were significantly up-regulated in MP receiving groups. In conclusion, M. pruriens can be used as a safe natural economic feed additive and a low inclusion level of 2 g/kg diet is recommended to improve growth, enhance immunity, maintain liver functioning, improve testicular development, and to modulate immune-related genes in the mono-sex O. niloticus . Highlights: Mucuna pruriens dietary inclusion modulates growth, immunity, and liver function in O. niloticus. Dietary incorporation with MP has a hypoglycemic effect. Two gram of MP elevatesGSI, testosterone levels, and maintains testicular architecture. Supplemented diet with MP up-regulates the immune-related genes.